Register Pemasaran Kosmetik pada Tiktok Live @mopbeauty - Rahayu, Ananda Dwi; Baehaqi, Imam (Hasta Wiyata, 2025)
The dynamic use of language by speakers creates diverse language variations. Language variation is classified based on its users and also based on its usage. Language variation based on its usage is also called register. Register is used in various human activities, one of which is the buying and selling transactions. In the digital era, buying and selling transactions are also conducted on social media. One such transaction activity on social media is carried out by the cosmetic brand MOP Beauty. By using the Tiktok Live and Tiktok Shop features, a language register can be found. Using the listening method with the free listening technique and note-taking technique, data on the registers found during the Tiktok Live session of @mopbeauty was collected. The data was then analyzed using a combination of matching and distribution methods. The data is then presented informally by detailing the findings using linguistic theories and references from previous research. The findings of this research include closed context registers, open context registers, and several linguistic registers. In addition to outlining the three types of registers found on TikTok Live @mopbeauty, this study also analyzes the functions of these registers.